The Sipakatau dalam Masyarakat Bugis Bone Perspektif Al-Quran - SUBHAN BAKRI (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2020)
As the times and advances in human civilization, the noble values ​​of culture began to be forgotten by the current generation. Sipakatau culture has become one of the cultures that is almost forgotten by Bugis humans. The term sipakatau which means